Transcriptional regulation by the ubiquitin system in model plant Arabidopsis thaliana - Hanczaryk, Katarzyna (Trinity College (Dublin, Ireland). Department of Genetics, 2014)
In eukaryotes, the ubiquitin (Ub) system controls protein stability and regulates many developmental and physiological processes, in part through the regulation of transcription. Recent data show that some components of the Ub system act as bona fide transcriptional co-activators by removing from the promoter of target genes ‘spent’ transcription factors that have become inactive after promoting transcription. After degradation of the ‘spent’ transcription factor, a ‘fresh’ and active one binds to the promoter of target genes to maintain transcription. More cases of such regulation by components of the Ub system have been emerged recently, including the first one in plants. Indeed, it has been shown that the protein UNUSUAL FLORAL ORGANS (UFO) in the model plant Arabidopsis thaliana acts as a transcriptional co-activator of the transcription factor LEAFY (LEY) in the regulation of flower development. UFO is an F-box protein, which is part of so-called SCF complexes. The latter are E3 ligases, whose function is to recognize a substrate and target it for degradation in a Ub- dependent manner.
Keywords: Genetics, Ph.D.; Ph.D. Trinity College Dublin